Daya Tarik Wisata Waduk Panji Sukarame Sebagai Objek Wisata di Kota Tenggarong - Uhai, Sabalius; Sukmana, Eman; Dwiatmojo, A Rinto; Anggriawan , Egi Saltia; Sinaga, Firman (Samarinda State Polytechnic, 2021)
The purpose of this study was to determine the tourist attraction in Waduk Panji Sukarame. Tenggarong City has one of the mainstay tourist destinations in East Kalimantan, one of which is the Waduk Panji Sukarame as a tourist attraction, as a tourist attraction and object, it is necessary to hold a good management process so that visitors become interested in coming to the place. This study finds out what tourist attractions are in the Waduk Panji Sukarame Tenggarong, Kutai Kartanegara Regency, East Kalimantan. The research method used is the descriptive qualitative research method. The data collected is through direct observation and interviews with the managers of the Waduk Panji Sukarame. Waduk Panji Sukarame has natural attractions. It has an orchid garden and has artificial gazebo tours, colourful bridges, unique toilets, flying fox, duck bikes, viewing towers, playgrounds. The Waduk Panji Sukarame has a tourist attraction and is worthy as a tourist attraction.